Carbamazepine coated silver nanoparticles for the simultaneous electrochemical sensing of specific food toxins. (1st June 2018) - Shah, Afzal; Malik, Maria Saleem; Zahid, Anum; Iftikhar, Faiza Jan; Anwar, Ayaz; Akhter, Mohammad Salim; Shah, Muhammad Raza; Zia, Muhammad Abid; Ashiq, Muhammad Naeem; Shah, Aamir Hassan
Abstract: Monitoring the use of colored additives in food commodities due to their potential carcinogenic effects is important for regulating their safe use. Herein, we test the cytotoxicity of food dyes against human neuroblastoma cell (SH-SY5Y) and report the development and applications of a novel and sensitive electrochemical sensor based on carbamazepine functionalized silver nanoparticles (Cbz-AgNPs) for the simultaneous detection of two toxic food dyes; Orange II and Rhodamine B. The characterization of Cbz-AgNPs was performed by UV–Vis spectrophotometry, atomic force microscopy (AFM) and FT-IR analysis. Small size, large surface area and high conductivity of AgNPs while host-guest complexation ability of Cbz with dyes are the unique properties which when harnessed together in the form of Cbz-AgNPs are responsible for sensitive detection of the said toxins. Successful modification of electrode surface was ensured from electrochemical impedance spectroscopy. The nanocomposite (Cbz-AgNP/GCE) based sensor was found to boost the oxidation signals of analytes remarkably as compared to individual Cbz or nanoparticles AgNPs modified electrodes. Detection limits measured as 1.2 nM for OR II and 1.0 nM for RB point towards excellent sensitivity of nanocomposite modified electrode. Low cost, easy fabrication, high sensitivity, and absolute discriminating ability for toxins even in the presence 200 times higher concentration of interfering agents than the analytes are unique characteristics which render the developed novel sensor highly favorable for the detection of food toxins. Theoretical calculations were done using ADF and results favored the experimental work.